Penile Mondor's disease- an understated entity - Jeremy Wild; Liam Wilson; Mohit Bajaj (Urology Case Reports, 2020)
We present a case of Penile Mondor's Disease (PMD) in a 36-year old male patient. PMD is an under-recognised and uncommon condition which presents with pain on erection and cord-like thickening of the dorsum of the penis. The diagnosis of PMD is usually confirmed with ultrasound imaging. The course of PMD is self-limiting, with multiple adjunct treatments proposed to hasten the recovery process however the evidence to support these treatments is limited.It is important both Primary Care Providers and Urologists are aware of this condition in order to provide appropriate information to patients regarding treatment options and prognosis.